Innovative research for organic 3.0 - Volume 2: Proceedings of the scientific track at the Organic World Congress 2017, November 9-11 in Delhi, India - Gerold Rahmann; C. Andres; A. K. Yadav; R. Ardakani; H. B. Babalad; N. Devakumar; S. L. Goel; V. Olowe; N. Ravisankar; J. P. Saini; G. Soto; H. Willer (Johann Heinrich von Thünen-Institut, 2017)
[Foreword] The future challenges in food production and consumption appear clear: * Feed 9 to 11 billion people in the next 30 to 80 years with enough, affordable and healthy food. * Protect the environment (e.g. soils, water, air, biodiversity and landscapes) whilst increasingly under pressure to achieve greater levels of intensification. * Mitigate greenhouse gas emissions and adapt to climate change in all farming systems and value chains. * Incorporate novel ethics, food habits, demographics and lifestyles into the food chains. * Produce food on limited farmland and fossil (non-renewable) resources efficiently and profitably. - Several findings from scientific research and practical applications suggest that organic food and farming systems can help in tackling these future challenges.1The 'low external input' approach, risk minimizing strategies and ethically accepted production practices of organic food and farming systemscan help to produce more affordable food for an increasing number of people while minimizing environmental impacts. However, resource efficiency, low-meat diets and reducing food waste are also essential factors that have to be considered. From a global perspective, organic food and farming systems is still a niche sector, as less than 1% of global farmland is managed organically and only a small proportion of the global population is consuming organic food in significant amounts. Production yields are relatively low, and the goals of organic food and farming systems, described in the principles and standards, are not achieved on every farm. This needs further development based on scientific evidence and good management practices. A lot has been done already to develop organic food and farming systems. Nevertheless, to assure, that organic food and farming systems becomes a significant part of the solutions for the future challenges in the food and farming sector, there is still much to do. The Scientific Track at the Organic World Congress 2017 in Delhi, India, will contribute to the global discussion on Organic 3.0, and taking the opportunity to answers some of the challenges in the context of the Indian subcontinent in particular. After a double-blind review, done by 120 reviewers from various disciplines from many experienced research institutions throughout the world, about 183 papers from 50 countries have been accepted. [...]
urn:nbn:de:gbv:253-201711-dn059308-2
Keywords: 630